FGF23 Actions on Target Tissues—With and Without Klotho - Richter, Beatrice; Faul, Christian (Frontiers in Endocrinology, 2018)
Fibroblast growth factor (FGF) 23 is a phosphaturic hormone whose physiologic actions on target tissues are mediated by FGF receptors (FGFR) and klotho, which functions as a co-receptor that increases the binding affinity of FGF23 for FGFRs. By stimulating FGFR/klotho complexes in the kidney and parathyroid gland, FGF23 reduces renal phosphate uptake and secretion of parathyroid hormone, respectively, thereby acting as a key regulator of phosphate metabolism. Recently, it has been shown that FGF23 can also target cell types that lack klotho. This unconventional signaling event occurs in an FGFR-dependent manner but involves other downstream signaling pathways than in “classic” klotho-expressing target organs. It appears that klotho-independent signaling mechanisms are only activated in the presence of high FGF23 concentrations and result in pathologic cellular changes. Therefore, it has been postulated that massive elevations in circulating levels of FGF23, as found in patients with chronic kidney disease, contribute to associated pathologies by targeting cells and tissues that lack klotho. This includes the induction of cardiac hypertrophy and fibrosis, the elevation of inflammatory cytokine expression in the liver, and the inhibition of neutrophil recruitment. Here, we describe the signaling and cellular events that are caused by FGF23 in tissues lacking klotho, and we discuss FGF23’s potential role as a hormone with widespread pathologic actions. Since the soluble form of klotho can function as a circulating co-receptor for FGF23, we also discuss the potential inhibitory effects of soluble klotho on FGF23-mediated signaling which might - at least partially - underlie the pleiotropic tissue-protective functions of klotho.